Zhilong Huoxue Tongyu capsule attenuates intracerebral hemorrhage induced redox imbalance by modulation of Nrf2 signaling pathway - Mazhar, Maryam; Yang, Guoqiang; Xu, Houping; Liu, Yulin; Liang, Pan; Yang, Luyin; Spáčil, Roman; Shen, Hongping; Zhang, Dechou; Ren, Wei; Yang, Sijin (Frontiers in Pharmacology, 2023)
Background: One of the severely debilitating and fatal subtypes of hemorrhagic stroke is intracerebral hemorrhage (ICH), which lacks adequate cure at present. Zhilong Huoxue Tongyu (ZLHXTY) capsule has been utilised effectively since last decade to treat ICH, in some provinces of China but the scientific basis for its mechanism is lacking. Purpose: To investigate the neuroprotective role of ZLHXTY capsules for ICH induced oxidative injury through the regulation of redox imbalance with the Nrf2 signalling pathway. Methods: Autologous blood injection model of ICH in C57BL/6J mice was employed. Three treatment groups received ZLHXTY once daily through oral gavage at doses 0.35g/kg, 0.7g/kg, and 1.4g/kg, started after 2 hrs and continued for 72hrs of ICH induction. The neurological outcome was measured using a balance beam test. Serum was tested for inflammatory markers IL-1β, IL-6, and TNF-α through ELISA, oxidative stress through hydrogen peroxide content assay, and antioxidant status by total antioxidant capacity (T-AOC) assay. Nuclear extract from brain tissue was assayed for Nrf2 transcriptional factor activity. RT-qPCR was performed for Nfe2l2, Sod1, Hmox1, Nqo1, and Mgst1; and western blotting for determination of protein expression of Nrf2, p62, Pp62, Keap, HO1, and NQO1. Fluoro-jade C staining was also used to examine neuronal damage. Results: ZLHXTY capsule treatment following ICH demonstrated a protective effect against oxidative brain injury. Neurological scoring showed improvement in behavioral outcomes. ELISA based identification demonstrated a significant decline in the expression of serum inflammatory markers. Hydrogen peroxide content in serum was found to be reduced. The total antioxidant capacity was also reduced in serum, but the ZLHXTY extract showed a concentration dependent increase in T-AOC speculating at its intrinsic antioxidant potential. Nrf2 transcriptional factor activity, mRNA and protein expression analyses revealed normalization of Nrf2 and its downstream targets, which were previously elevated as a result of oxidative stress induced by ICH. Neuronal damage was also reduced markedly after ZLHXTY treatment as revealed by Fluoro-jade C staining. Conclusion: ZLHXTY capsules possess an intrinsic antioxidant potential that can modulate the ICH induced redox imbalance in the brain as revealed by the normalization of Nrf2 and its downstream antioxidant targets.